Shaping ability of rotary instrumentation techniques and their limitations in simulated root canals - Maria Giraki; Edith Harapetian; Stefan Rüttermann; Susanne Gerhardt-Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
The aim of this in vitro study was to describe the shaping ability of rotary nickel-titanium (NiTi) instruments (Mtwo, VDW, Munich, Germany) with benefi cial properties in combination with two different endodontic devices (Mtwo direct and Endo IT professional) and to compare them with Mity NiTi K-Files (Loser, Leverkusen, Germany) in combination with preparation by hand in severely curved simulated root canals of acrylic blocks Thirty blocks simulating a severely curved root canal were divided into three groups (n=10 for each). All canals were prepared with NiTi fi les to an ISO size of 40 using an apical-coronal preparation technique. Mtwo NiTi fi les were used for the automatic systems, while Mity K-Files were used for the preparation by hand.